Effects of Extraction Media on Protein Isolates of Some Gourd Melon (Egusi) Seeds - Ogundele, J.O.; Sanni, T.A.; Oshodi, A.A.; Okuo, J.M.; Amoo, I.A. (Pakistan Journal of Nutrition, 2015)
Protein isolates of Citrullus colocynthis, Citrullus vulgaris, Lageneria siceraria I (African Wine Kettle gourd), Lagenaria siceraria II (Basket Ball gourd) and Lageneria siceraria III (Bushel Giant Gourd) melon seeds were prepared using sodium sulphite extraction followed by precipitation at the isoelectric points of the seeds. Proximate composition of the isolates were determined using standard methods. Protein contents (%) of the protein isolates are relatively high, with values: 89.04, 89.44, 93.96, 90.42 and 90.63 (%) for Citrullus colocynthis, Citrullus vulgaris, Lageneria siceraria I, Lagenaria siceraria II and Lageneria siceraria III melon seeds protein isolates, respectively. The fat, fibre and carbohydrate contents of the protein isolates are however, relatively low.